1999
DOI: 10.1071/a98103
|View full text |Cite
|
Sign up to set email alerts
|

Measuring yield loss in cereals caused by root lesion nematodes (Pratylenchus neglectus and P. thornei) with and without nematicide

Abstract: Yield loss caused by root lesion nematodes (Pratylenchus neglectus and P. thornei) was measured using the nematicide aldicarb (Temik 150GTM) or by correlating yield with initial or final nematode densities. In 1996, rotation trials (1 P. neglectus and 1 P. thornei) were established with susceptible and moderately resistant wheat varieties and resistant barley and triticale varieties. An intolerant oat variety (cv. Echidna) was planted over all plots in 1997. Nematode densities were 90% (P. neglectus) or 95% (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…High populations of P. thornei cause up to 85% yield loss in wheat (Triticum aestivum L.) varieties (Thompson et al 1993). Similarly, P. neglectus causes up to 27% yield loss in wheat varieties (Taylor et al 1999). In Australia, annual lost wheat production caused by P. thornei and P. neglectus is estimated at $36 million and $12 million, respectively (Brennan and Murray 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…High populations of P. thornei cause up to 85% yield loss in wheat (Triticum aestivum L.) varieties (Thompson et al 1993). Similarly, P. neglectus causes up to 27% yield loss in wheat varieties (Taylor et al 1999). In Australia, annual lost wheat production caused by P. thornei and P. neglectus is estimated at $36 million and $12 million, respectively (Brennan and Murray 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Glasshouse screening of wheat lines inoculated with pure cultures of nematodes has suggested that the genetic mechanisms that confer resistance to P. thornei do not confer resistance to P. neglectus (Farsi et al 1995;Taylor et al 1999). However, mixed populations of both species can occur in the same field and therefore breeding wheat varieties with resistance to both species of nematode is a desirable goal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight species of the genus Pratylenchus infest small grains (Rivoal & Cook, 1993;Nicol et al, 2004). Among them, P. thornei Sher and Allen, 1953, P. neglectus (Rensch, 1924) Filipjev and Schuurmans Stekhoven, 1941, P. penetrans (Cobb, 1971) Filipjev and Schuurmans Stekhoven, 1941and P. crenatus Loof, 1960 have a worldwide distribution and can cause substantial yield losses (Taylor et al, 1999;Nicol et al, 2004). RLN hatch from the egg as a second-stage juvenile and starts feeding on the plant.…”
Section: Introductionmentioning
confidence: 99%